Analisis Fatwa No.17/DSN-MUI/IX/2000 Terhadap Penerapan Denda Keterlambatan Pembayaran Angsuran Dalam Akad Pembiayaan Murabahah Di Perbankan Syariah - Mohamad Andi Syamsul Maula (Jurnal Ilmiah Ekonomi Islam, 2023)
The development of Islamic banks in Indonesia is quite significant, this is indicated by the increasing number of Islamic banking institutions that have been established. From a number of sharia bank products, the most widely used product is murabaha financing. The purpose of this study was to find out the mechanism for applying fines for late installment payments in Islamic banks by referring to fatwa No. 17/DSN-MUI/IX/2000 Concerning Sanctions for able customers who delay financing are considered appropriate. This paper uses a descriptive analytical method with secondary data sources in the form of books, articles and documents from the internet, either from the OJK website or other valid sources. The results of this study state that this has an impact on Islamic banks, namely on increasing vigilance in managing murabahah financing, and for customers the application of fines for murabahah financing has an educative and preventive function.